Genealogy, critique, and decolonisation: Ibn Khaldun and moving beyond filling the gaps [version 2; peer review: 1 approved, 2 approved with reservations] - Sertaç Sehlikoglu (Open Research Europe)
The aim of this paper is to locate critique at the intersections of the genealogy of knowledge in anthropological thinking and the decolonising movement. The paper approaches the decolonising movement as one of the most crucial points in anthropological thinking. It is built on the premise that the decolonising movement is set to go beyond filling the gaps in genealogies and it can do so by: (1) revising the ‘dismissed’ genealogies that have contributed to the formation of the contemporary classical theory and (2) thinking creatively in implementing the critical thinking tools to the dismissed scholarship, in an equal manner to the Eurocentric scholarship. To illustrate, it uses the case of Ibn Khaldun, an Arab scholar of social sciences and historical analysis from the 14th Century, often referred to as the first sociologist. On the one hand, his influence on classical Western thinking is largely dismissed. On the other hand, as a counter-response to this dismissal, the new Islamic revivalist intelligentsia in the Muslim right engages with him in a selective manner that not only rejects that central critical thinking but, even worse, sanctions the local regimes of power, including that local canon. By locating his scholarship to multiple tropes in anthropological theory and reading his evolutionist thinking vis-à-vis the post-colonial literature in anthropology and sociology, I question the limits and possibilities of critical thinking within and beyond the decolonising movement.